Current Weight Management Approaches Used by Primary Care Providers in Six Multidisciplinary Healthcare Settings in Ontario - Aboueid, Stephanie; Jasinska, Monika; Bourgeault, Ivy; Giroux, Isabelle (Université d'Ottawa | University of Ottawa, 2018)
Background Obesity management in primary care has been suboptimal due to lack of access to allied health professionals, time, and resources. Purpose To understand the weight management approaches used by primary care providers working in team-based settings and how they assess the most suitable approach for a patient. Methods A total of 20 primary care providers (13 nurse practitioners and 7 family physicians) working in 6 multidisciplinary clinics in Ontario were interviewed. All interviews were recorded, transcribed verbatim, and coded using NVivo qualitative software. Conventional content analysis was used to inductively elucidate codes, which were then clustered into categories. Results A referral to on-site programming was the most frequent weight management approach used. The pharmacological approach was underutilized due to adverse side effects and cost to patients. Primary care providers assessed the most suitable weight management approach based on patients': preference, level of motivation, income status and access to resources, body mass index and comorbidities, and previous weight loss attempts. Primary care providers perceived that referring to health professionals and educational resources were the approaches preferred by patients. Conclusions The team-based nature of these clinics allowed for referrals to various on-site professionals and/or programs. Some barriers to pursuing weight management avenues with patients were patient dependent.
Keywords: Canadian health services; Multiprofessional practice; obesity; primary care; qualitative approaches